Efficient Virtualization Schema for Load Management in Cloud Data Centers - Jaiswal, Sakshi (My University, 2018)
Cloud Computing provides a mechanism of delivering application as services and resources in data center that provides those services. Cloud computing gives a surrounding for sharing resources of different framework, application development platform, and middleware development platform and business application. The cloud services are flexible in terms of their usage i.e., pay-as-you-use. In this thesis, CPU performance of data center have been analysed on the basis of two datasets. Presently cloud computing framework supports/hosts millions of physical servers which produce lot of heat and consume more electricity. Thus, analyse the workload performance of cloud datacenter hosting business applications. Cloud Infrastructure as Service (CIAS) is a collection of services, which is used to automate the process of test failure reproduction. Virtual machines are used to reproduce model based test failures to improve productivity while performing failure analysis. In this thesis, it is explained that how virtual box is enabled in Cloud infrastructure to make much easier for developers to perform debugging or testing in its local machine without any delay for longer period of time.
Keywords: Virutal box; cloud computing; virtualization